Agrobiodiversity and crop diffusion in Morocco from Antiquity to the early Modern period (8th century bce–17th century ce): an archaeobotanical review - Jérôme Ros; Fatima-Ezzahra Badri; Ruth Pelling (Vegetation History and Archaeobotany, 2026)

Agricultural systems regulate plant and insect diversity and induce ecosystem novelty - Jessie Woodbridge; Ralph Fyfe; David Smith; Anne de Varielles; Ruth Pelling; Michael J. Grant; Robert Batchelor; Robert Scaife; James Greig; Petra Dark; Denise Druce; Geoff Garbett; et al. (Anthropocene, 2023)

Food, farming and trade on the Danube frontier: plant remains from Roman Aelia Mursa (Osijek, Croatia) - Kelly Reed; Tino Leleković; Lisa Lodwick; Rhona Fenwick; Ruth Pelling; Helmut Kroll (Vegetation History and Archaeobotany, 2022)
Archaeobotanical investigations at the Roman town of Aelia Mursa, located near the Danube frontier in modern day Croatia, have revealed an extraordinary assemblage of food remains from a series of pits dated to the early 2nd century ad . The site yielded a wide array of economically important food remains, including staples such as Hordeum (barley), Panicum miliaceum (broomcorn millet), Triticum aestivum (bread wheat), Secale cereale (rye), Lens culinaris (lentil) and Vicia faba (broad bean). We also found a range of fruits, nuts, herbs and vegetables, such as Daucus carota (carrot), Cichorium intybus (chicory), Allium sativum (garlic), Ficus carica (fig), Vitis vinifera (grape) and Olea europaea (olive). Further, we found clearly identifiable remains of eggshell, fish bones and scales, unidentifiable fruit flesh and porridge or bread remains, as well as possible animal dung. The site provides important evidence of exotic foods including Piper nigrum (pepper), Oryza sp. (rice) and Punica granatum (pomegranate). This diverse and unique assemblage provides a tantalising insight into the character of food, farming and trade of the people living on the frontier of the Roman Empire.

Exploring contamination (intrusion and residuality) in the archaeobotanical record: case studies from central and southern England - Ruth Pelling; Gill Campbell; Wendy Carruthers; Kath Hunter; Peter Marshall (Vegetation History and Archaeobotany, 2015)